Throughput and delay scaling laws for mobile overlaid wireless networks - Zhang, Wenjie (2013)
In this paper, we study the throughput and delay scaling laws over two coexisting mobile networks. The primary network consists of n randomly distributed primary nodes which can operate as if the secondary network is absent. However, the secondary network with a higher density m=nβ, β>1 is required to adjust its protocol. By considering that both the primary and the secondary networks move according to random walk mobility model, we propose a multi-hop transmission scheme, and show that the secondary network can achieve the same throughput and delay tradeoff scaling law as in stand-alone network Ds(m)=Θ(mλs(m)). Furthermore, for primary network, it is shown that the tradeoff scaling law is given by Dp(n)=Θ(√nlognλp(n)), when the primary node is chosen as relay node. If the relay node is a secondary node, the scaling law is Dp(n)=Θ(√nβlognλp(n)). The novelties of this paper lie in: (i) detailed study of the delay scaling law for the primary network in the complex scenario where both the primary and the secondary networks are mobile; (ii) the impact of buffer delay on the two networks due to the presence of preservation region. We explicitly analyze the buffer delay and obtain an expression as DsrII(m)=Θ(1/√nβ-1αs(m)).